What is the product? (x 3)(2 x minus 1) 2 x squared minus 3 2 x squared 6 x 2 x squared 5 x minus 3 2 x squared 6 x minus 3.

Respuesta :

The product of the function is 2x^2+ 5x - 3

We are to find the product of the functions x + 3 and 2x -1

  • let f(x) = x+ 3
  • g(x) = 2x - 1

Taking the product:

f(x)g(x) = (x+3)(2x -1)

f(x)g(x) = x(2x) - x(1) + 3(2x) + 3(-1)

f(x)g(x) = 2x^2 - x + 6x - 3

f(x)g(x) = 2x^2+ 5x - 3

Hence the product of the function is 2x^2+ 5x - 3

Learn more on product of functions here: https://brainly.com/question/25638609

Answer:

c

Step-by-step explanation: